Student's essential guide to .NET - Grimer, Tony. (Oxford : Butterworth-Heinemann, 2004)
The Student's Essential Guide to .NET provides a clear and simple overview of Microsoft's .NET technologies. It is aimed at second and third year undergraduate students and postgraduate students on Computing or Computer Science courses who are required to look at a modern operating system, (Microsoft Windows 9x, Nt 2000 or XP) and to design and code simple or even not so simple examples. The approach is based upon the student's learning the technology of .NET through examples using the supported languages CΔ, VB and C++. The examples are based on fun, familiar games, and students are encouraged to review reference material to refine their skills on key aspects of the architecture. Review questions and worked examples enhance the learning process and the material is supported by the author's website, which contains extensive ancillary material. * Student-focused treatment with many examples and exercises, together with solutions * Integrates the use of .NET with the supported languages CΔ, VB and C++ * Authors supporting website contains solutions, source code and other extras.
An overview of .NET -- The common language runtime -- The framework class library and other support functionality -- Supported programming languages -- Windows Forms -- NET components -- Interoperability issues -- The role of XML -- ADO.NET -- Networking, web forms and ASP.NET -- Web services -- The case study.
Includes index.
Keywords: Microsoft .NET.; Electronic books